The Socratic Imperative and Philosophical Autonomy - Mircea TOBOȘARU (Studia Universitatis Babeș-Bolyai. Philosophia, 2025)
The Socratic imperative to examine one's own life is linked to the fundamental moral idea of personal autonomy. Therefore, it is quite difficult to reject it, but it is equally challenging to apply it for various reasons. If it is philosophically assumed, a distilled version of the Socratic imperative has significant implications for one’s meta-philosophical options and the way we conceive of philosophical education. I argue that a commitment to the Socratic imperative implies a commitment to what I call “philosophical autonomy”, namely an intellectual obligation to map the space of (meta-)philosophical options and position oneself in the dialectical theoretical space as close as possible to those philosophical subjects that are relevant for the task of examination of one’s life.